THE INFLUENCE OF FINANCIAL LITERACY, RELIGIOSITY, AND BRAND IMAGE ON MILLENNIAL INTEREST IN ISLAMIC INSURANCE: AN EMPIRICAL STUDY IN SOUTH JAKARTA - Effi Abidah, Erina; Mihajat, Muhammad Iman Sastra (UIN Sunan Gunung Djati Bandung, 2025)
This research investigates the impact of financial literacy, religiosity, and brand image on the millennial generation's desire to use Islamic insurance in South Jakarta. This research employs a quantitative methodology via a survey instrument, with 100 participants chosen via purposive selection. Surveys gathered data, which SPSS software analysed using multiple linear regression. The study findings indicate that financial literacy, religiosity, and brand image greatly affect the millennial generation's interest in using Islamic insurance, contributing 53% to this desire. This effect arises when financial literacy improves comprehension of the product, religiosity fosters the alignment of financial choices with spiritual beliefs, and brand image cultivates confidence in service providers. Conversely, the other 47% is shaped by external variables like economic circumstances, cultural influences, individual motivation, and product accessibility, which impact consumer choices. This research suggests that we should enhance digital financial literacy, strengthen brand image, and include Islamic principles in services to increase millennial interest in Islamic insurance.